MARGOV – building social sustainability - Vasconcelos, Lia (2019)
Structured in three components - Governance, Citizenship and Dynamic-Spatial Structure – the MARGov project aims to build a Model of Collaborative Governance for Marine Protected Areas using as case study the Marine Park Professor Luiz Saldanha. The objective is to empower local communities enabling them to be agents for change for the sustainable governance of the Ocean, through an eco-social dialogue supported by active participation. This intends to reinforce competences and the co-responsibility of all the actors involved. In this paper the authors present the work developed in the first component – Governance – essential to assure social sustainability. A successful Marine Protected Area strongly depends on the balance between man and environment, and therefore, on the eco-social dialogue that is possible to be established among all actors. According to the literature, the building up of participatory formats that assure the articulation between different groups, enhancing the constructive dialogue aiming at achieving sustainable management, contributes to the overlay of knowledge and different perspectives, and generates enriched and more robust solutions. It also says that such processes generate new synergies and potentiate the exchange of ideas, experiences, technical-scientific cooperation, as well as the integration of knowledge and good practices, and that they frequently create the conditions for the emergence of innovative alternatives. This paper is about the participatory sessions created and conducted as part of the Governance component of the project, describing the methodology developed for the expanded involvement of local communities aiming at building a model of Collaborative Governance. It also presents the strategy developed by the MARGov team to reinforce the social component, through continuous improvement of a communication strategy and the setting up of a constructive participatory process. Finally, it presents the results of the dialog generated in these fora and it discusses all this in the context of a general conceptual framework. It also identifies what made an actual difference, and the lessons learned, theorizing from action and exploring how to pursue.